2019
DOI: 10.1161/jaha.118.011648
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Between American Heart Association's Life's Simple 7, ECG Silent Myocardial Infarction, and Cardiovascular Mortality

Abstract: Background We examined the interrelationships among cardiovascular health (CVH), assessed by the American Heart Association's Life's Simple 7 (LS7) health metrics, silent myocardial infarction (SMI), and cardiovascular disease (CVD) mortality. Methods and Results This analysis included 6766 participants without a history of coronary heart disease from the Third Report of the National Health and Nutrition Examination Survey. Poor, intermediate, and ideal CVH were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…As previously noted, several studies have addressed the utility of the Life’s Simple 7 scale for predicting adverse vascular outcomes and mortality across different races/ethnic groups and populations ( Ahmad et al, 2019 , Ahmed et al, 2020 , Del Brutto et al, 2013a , Dong et al, 2012 , Folsom et al, 2011 , Han et al, 2019 , Lin et al, 2015 , Patterson et al, 2016 , Zhang et al, 2020 ). In the multi-ethnic Northern Manhattan Study, the HR for all-cause mortality was not significantly lower for individuals with five or more ideal CVH metrics when compared to that of those with two ideal metrics (0.59 [95% C.I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously noted, several studies have addressed the utility of the Life’s Simple 7 scale for predicting adverse vascular outcomes and mortality across different races/ethnic groups and populations ( Ahmad et al, 2019 , Ahmed et al, 2020 , Del Brutto et al, 2013a , Dong et al, 2012 , Folsom et al, 2011 , Han et al, 2019 , Lin et al, 2015 , Patterson et al, 2016 , Zhang et al, 2020 ). In the multi-ethnic Northern Manhattan Study, the HR for all-cause mortality was not significantly lower for individuals with five or more ideal CVH metrics when compared to that of those with two ideal metrics (0.59 [95% C.I.…”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal studies have also addressed the influence of Life’s Simple 7 on mortality ( Ahmad et al, 2019 , Dong et al, 2012 , Han et al, 2019 , Lin et al, 2015 ). However, information on the value of this scale in predicting mortality among people living in remote or rural communities is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are few publications on type 1 diabetes that explore clustering, it has been demonstrated that the clustering of favourable AHA health metrics is associated with lower CVD and cardiovascular mortality in general populations [ 8 10 ]. In the National Health and Nutrition Examination Survey (NHANES III), participants with ideal cardiovascular health had a 69% lower risk of developing a silent myocardial infarction, as detected by ECG (OR [95% CI] 0.31 [0.12, 0.75]) [ 10 ]. Similarly, the Australian Health Survey found an inverse association between a higher number of ideal metrics and a lower risk of prevalent ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ideal values of each of these cardiovascular health metrics were specified, based on the literature and the recommendations of previous committees. A score is assigned based on the number of ideal cardiovascular health metrics, and studies in general populations have shown that higher scores are associated with lower risks of CVD [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are often unaware of their illness and do not limit their activities. With SMI, the incidence of heart failure was significantly increased (20,22), and the effects of high-risk factors, such as smoking, reduced physical activity, high body mass index, poor dietary habits, hypertension, hyperlipidaemia and hyperglycaemia, on cardiovascular disease were almost doubled (23). If clinically manifested acute myocardial infarction patients were found to have prior SMI by late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) images, they would have a more than 3-fold risk of mortality and major adverse cardiovascular events (21).…”
Section: Discussionmentioning
confidence: 99%